A Philological Study of The Tanjung Barulak Tarekat Manuscript in Arabic and Pegon Arabic - Hanif, Akhyar; Afrina, Cut; Rudiamon, Septika; Mudinillah, Adam; Deswita, Deswita; Rahmi, Elvi (Arabiyat : Jurnal Pendidikan Bahasa Arab dan Kebahasaaraban, 2024)
This paper aims to analyze the text in the Tanjung Barulak Sufi manuscript, Tanah Datar district. This study uses a philological research method with the object of study being a manuscript with the code 02/BB.II/twf/2021. This method has six working steps: manuscript inventory, manuscript description, manuscript grouping and comparison, selection of text edition methods, transliteration, and additional studies. This study reveals four main teachings of the Naqsyabandiyah Sufi order, first, absolute obedience to the teacher based on the terminology of the text "believe in Allah and the Prophet and the teacher", "uphold the command of Allah and the command of the Prophet and the command of the teacher and stay away from the command of Allah and the command of the Prophet and the command of the teacher". Second, dhikr by saying lâ ilâha illallâh. Third, zuhud means setting aside worldly affairs when we perform rituals of worship to Allah. And fourth, tauhid, namely adhering firmly to the i'tikad of the Qadariyah and Jabbariyah people.